The Association Between Systemic Inflammatory Markers and Post-Stroke Depression: A Prospective Stroke Cohort - Hu J (Dove Medical Press, 2021)
Jingjie Hu,* Liuyuan Wang,* Kaili Fan, Wenwei Ren, Qiongzhang Wang, Yiting Ruan, Chengxiang Yuan, Guiqian Huang, Jincai He Department of Neurology, The First Affiliated Hospital of Wenzhou Medical University, Wenzhou, 325000, Zhejiang, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jincai He; Guiqian HuangDepartment of Neurology, The First Affiliated Hospital of Wenzhou Medical University, Wenzhou, 325000, Zhejiang Province, People’s Republic of ChinaTel +86 577-555780166; +86 577-555781380Fax +86 577-55578033; +86 577-55578999Email hjc@wmu.edu.cn; huangguiqian123@126.comObjective: Inflammation plays an important role in stroke. Many inflammatory markers in peripheral blood are proved to be associated with stroke severity or prognosis. But few comprehensive models or scales to evaluate the post-stroke depression (PSD) have been reported. In this study, we aimed to compare the level of systemic inflammation markers between PSD and non-PSD patients and explore the association of these inflammatory markers with PSD.Methods: Totally, 432 ischemic stroke patients were consecutively enrolled in the study and received 1 month follow-up. We used the 17-Hamilton Rating Scale to measure depressive symptoms at 1 month after stroke. With the Hamilton Depression Scale score of > 7, patients were diagnosed with PSD. Systemic immune-inflammation index (SII), neutrophil-to-lymphocyte (NLR), platelet-to-lymphocyte (PLR) and derived neutrophil-to-lymphocyte ratio (dNLR) were calculated from the admission blood work.Results: Finally, 129 patients (30.5%) were diagnosed with PSD at 1 month. PSD patients showed significantly higher levels of SII (501.27 (345.43– 782.58) vs 429.60 (315.64– 570.98), P=0.001), NLR (2.36 (1.77– 3.82) vs 2.17 (1.56– 2.80), P=0.010), dNLR (1.67 (1.30– 2.51) vs 1.54 (1.16– 1.99), P=0.009), PLR (124.65 (95.25– 155.15) vs 109.22 (92.38– 142.03), P=0.015), especially SII at admission as compared to non-PSD patients. In the logistic analysis, SII value (> 547.30) was independently associated with the occurrence of PSD (OR=2.181, 95% CI=1.274– 3.732, p =0.004), better than dNLR (OR=1.833, 95% CI=1.071– 3.137, p =0.027), PLR (OR= 1.822, 95% CI=1.063– 3.122, p =0.029) and NLR (OR =1.728, 95% CI=1.009– 2.958, p =0.046).Conclusion: Increased SII, PLR, dNLR, NLR, particularly SII at admission, are significantly correlated with PSD and may add some prognostic clues to find early discovery of PSD.Keywords: inflammatory markers, post-stroke depression, systemic immune-inflammation index, neutrophil-to-lymphocyte, platelet-to-lymphocyte, derived neutrophil-to-lymphocyte ratio